2019
DOI: 10.1055/s-0039-3400972
|View full text |Cite
|
Sign up to set email alerts
|

A Compendium of Core Lexicon Checklists

Abstract: Core Lexicon (CoreLex) is a relatively new approach assessing lexical use in discourse. CoreLex examines the specific lexical items used to tell a story, or how typical lexical items are compared with a normative sample. This method has great potential for clinical utilization because CoreLex measures are fast, easy to administer, and correlate with microlinguistic and macrolinguistic discourse measures. The purpose of this article is to provide clinicians with a centralized resource for currently available Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…All transcripts had previously been scored by the authors for main concept production using the Richardson and Dalton checklists. 6,64 They were scored for CoreLex production according to the checklists reported by Dalton and Richardson 65 and Dalton et al 68 Discourse sample lengths for efficiency calculations were retrieved using the EVAL tool in the Computerized Language ANalysis (CLAN) software available through AphasiaBank.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All transcripts had previously been scored by the authors for main concept production using the Richardson and Dalton checklists. 6,64 They were scored for CoreLex production according to the checklists reported by Dalton and Richardson 65 and Dalton et al 68 Discourse sample lengths for efficiency calculations were retrieved using the EVAL tool in the Computerized Language ANalysis (CLAN) software available through AphasiaBank.…”
Section: Discussionmentioning
confidence: 99%
“…This issue includes a tutorial on CoreLex 51 which reviews how core lexicons are developed and might be applied by clinicians, and a compendium of CoreLex checklists for various stimuli. 68 CoreLex is scored by assigning one point for each checklist item produced by a participant. Synonyms of CoreLex items are not given points, but inflected CoreLex items are.…”
Section: Core Lexiconmentioning
confidence: 99%
See 1 more Smart Citation
“…See Appendices in the study by Dalton et al for core lexicon checklists reported by previous studies. 66…”
Section: Validity and Reliability Of Core Lexicon Measuresmentioning
confidence: 99%
“…In fact, this issue features several articles on the use of core lexicons and their application to aphasia, extending the scope of earlier work that examined the top 10 nouns and verbs in participants' responses to the procedural discourse and Cinderella story telling tasks from the AphasiaBank discourse protocol (see articles by Dalton et al and Kim et al in this issue). [23][24][25][26][27] Dalton and Richardson analyzed responses to the Broken Window picture description task from the AphasiaBank discourse protocol. 7 They created a core lexicon (CoreLex) list of the 24 unique lemmas (word roots, such as "run" for "runs," "running" and "ran") used by at least 50% of the normative sample (92 control participants).…”
Section: For Morementioning
confidence: 99%